Comparison of the Blood-Brain Barrier Transport and Vulnerability to P-Glycoprotein-Mediated Drug-Drug Interaction of Domperidone versus Metoclopramide Assessed Using In Vitro Assay and PET Imaging - Louise Breuil; Sébastien Goutal; Solène Marie; Antonio Del Vecchio; Davide Audisio; Amélie Soyer; Maud Goislard; Wadad Saba; Nicolas Tournier; Fabien Caillé (MDPI AG, 2022)
Domperidone and metoclopramide are widely prescribed antiemetic drugs with distinct neurological side effects. The impact of P-glycoprotein (P-gp)-mediated efflux at the blood-brain barrier (BBB) on brain exposure and BBB permeation was compared in vitro and in vivo using positron emission tomography (PET) imaging in rats with the radiolabeled analogs [11C]domperidone and [11C]metoclopramide. In P-gp-overexpressing cells, the IC50 of tariquidar, a potent P-gp inhibitor, was drastically different using [11C]domperidone (221 nM [198-248 nM]) or [11C]metoclopramide (4 nM [2-8 nM]) as the substrate. Complete P-gp inhibition led to a 1.8-fold higher increase in the cellular uptake of [11C]domperidone compared with [11C]metoclopramide (p < 0.0001). Brain PET imaging revealed that the baseline brain exposure (AUCbrain) of [11C]metoclopramide was 2.4-fold higher compared with [11C]domperidone (p < 0.001), consistent with a 1.8-fold higher BBB penetration (AUCbrain/AUCplasma). The maximal increase in the brain exposure (2.9-fold, p < 0.0001) and BBB penetration (2.9-fold, p < 0.0001) of [11C]metoclopramide was achieved using 8 mg/kg of tariquidar. In comparison, neither 8 nor 15 mg/kg of tariquidar increased the brain exposure of [11C]domperidone (p > 0.05). Domperidone is an avid P-gp substrate that was in vitro compared with metoclopramide. Domperidone benefits from a lower brain exposure and a limited risk for P-gp-mediated drug-drug interaction involving P-gp inhibition at the BBB.